FOREIGN MARKET ENTRY STRATEGIES USED BY MULTINATIONAL CORPORATIONS IN KENYA: A CASE OF COCA COLA KENYA LTD - Cheptegei, Daniel Kwemoi; Yabs, Dr. John (European Journal of Business and Strategic Management, 2016)
Purpose: The objective of the study was to establish the foreign market entry strategies adopted by Coca Cola Kenya Ltd. Methodology: The study employed a case study research design. Primary data was used in the research. The data was collected using an interview guide. The respondents interviewed were senior managers of Coca Cola Kenya Ltd in the operations department. Five senior managers were interviewed; The finance manager, the operations manager, the commercial manager, the exports manager and the Production Manager. Data was analysed using content analysis as the study aimed to collect data that was qualitative in nature. Results: Following the study findings it was possible to conclude that Coca Cola company has ventured into various foreign market entry strategies in order to increase its customer base and its profits. These market entry strategies include foreign direct investment, joint ventures, franchising and exporting. It was also possible to conclude that there are various factors influencing the choice of marketing strategy as an entry mode were the legal framework, risk of macroeconomic instability, loss of assets due to non-enforceability of contracts and physical destruction caused by armed conflicts. It was also possible to conclude that all market entry strategies faced various challenges but the management was successful in overcoming the challenges Unique contribution to theory, practice and policy: It is also recommended that the company should study the marketing environment before adopting any strategy so as venture into the strategies which best their company.